Musculoskeletal Manifestations of Sickle Cell Anaemia: A Pictorial Review - A. Ganguly; W. Boswell; H. Aniq (Anemia)
Sickle cell anaemia is an autosomal recessive genetic condition producing abnormal haemoglobin HbS molecules that result in stiff and sticky red blood cells leading to unpredictable episodes of microvascular occlusions. The clinical and radiological manifestations of sickle cell anaemia result from small vessel occlusion, leading to tissue ischemia/infarction and progressive end-organ damage. In this paper we discuss and illustrate the various musculoskeletal manifestations of sickle cell disease focusing primarily on marrow hyperplasia, osteomyelitis and septic arthritis, medullary and epiphyseal bone infarcts, growth defects, and soft tissue changes.